2014
DOI: 10.1111/jsap.12253
|View full text |Cite
|
Sign up to set email alerts
|

Are the fabellae bisected by the femoral cortices in a true craniocaudal pelvic limb radiograph?

Abstract: The accurate measurement of femoral varus angle is important in pre-surgical planning of distal femoral ostectomy. Radiography is normally used to obtain the femoral varus angle, and femoral rotational malpositioning will induce errors in the femoral varus angle measured. Bisection of the fabellae by the femoral cortices is commonly cited as a criterion by which to assess whether a radiographic projection is truly craniocaudal, yet this study has shown this not to be valid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…The criteria for the radiograph in frontal plane of the femur were that the hip was extended in neutral rotation, both femurs were parallel with the pelvis and the cassette, 50% of the lesser trochanter was seen at the medial aspect of the proximal femur and the vertical walls of the intercondylar notch were in distinct parallel lines. 17,32,33 For craniocaudal and caudocranial radiography of the tibia, the medial aspect of the tuber calcaneus was aligned with the intermediate tibial ridge. The criterion for correct positioning was percent deviation, which was the percentage of the distance between the medial aspect of the tuber calcaneus and the intermediate tibial ridge, divided by the distance between the two arciform grooves of the cochlea tibiae at its most proximal point.…”
Section: Frontal Planementioning
confidence: 99%
“…The criteria for the radiograph in frontal plane of the femur were that the hip was extended in neutral rotation, both femurs were parallel with the pelvis and the cassette, 50% of the lesser trochanter was seen at the medial aspect of the proximal femur and the vertical walls of the intercondylar notch were in distinct parallel lines. 17,32,33 For craniocaudal and caudocranial radiography of the tibia, the medial aspect of the tuber calcaneus was aligned with the intermediate tibial ridge. The criterion for correct positioning was percent deviation, which was the percentage of the distance between the medial aspect of the tuber calcaneus and the intermediate tibial ridge, divided by the distance between the two arciform grooves of the cochlea tibiae at its most proximal point.…”
Section: Frontal Planementioning
confidence: 99%
“…When assessing skeletal deformities, the possibility of carrying out MPR measurements allows for the minimization of artefacts related to reducing a threedimensional bone to a two-dimensional radiographic image. Moreover, it has been demonstrated that the bisection of the fabellae by the respective femoral cortices, obtained via radiography, is not an index of correct position in in the craniocaudal projection of the femur (28). Table 1 Descriptive analysis of the healthy population (Group A) and the population with medial patellar luxation (Group B), and a comparison between Group A and Group B.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that bisection of the medial and lateral fabellae by the corresponding femoral cortices is unreliable as an indicator of correct craniocaudal radiographic views of the femur in case of high grade MPL. 25 To eliminate the positioning error in dogs with distal Abbreviations: AA, angle of anteversion; aLDFA, anatomical lateral distal femoral angle; aLPFA, anatomical lateral proximal femoral angle; FIA, femoral inclination angle; FVA, femoral varus angle; MPL, medial patellar luxation; SD, standard deviation. Note: The mean values in the same row that have a different superscript lower case letter are significantly different (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%